Achieving Nepal’s sustainable development goals (SDGs) by effective compliance of corporate governance - B.K., Anish; Mahato, Anish; Thapa, Sajat; Rai, Ashish; Devkota, Niranjan (Quest Journal of Management and Social Sciences, 2019)
Background: it has been almost two that sustainable development has been a global agenda in a form or other. Nepal’s efforts to successful execution of millennium development goals (MDGs) also opened new paradigms for the enactment of sustainable development goals (SDGs) planned for 2016-2030. The MDGs based on millennium declaration in the year 2000 by the United Nations (UN) has set foundation for the SDGs 2016-2030. Objectives: The primary purpose of this discourse was to establish the relationship between effective compliance of corporate governance and Nepal’s potential for the attainment of SDGs 2016-2030. Methods: Fully based on desk review performed in a qualitative setting of inquiry. Results: There is positive relationship between effective compliance of corporate governance (CG) and potential for the attainment of SDGs 2016-2030 in changing context of Nepal. Further, this paper highlights the general national scenarios, issues, challenges and ways forward in governing sustainable corporate development in Nepal to contribute the nation in its mission to attainment of sustainable development goals 2016-2030. Conclusions: Effective compliance of corporate governance serves as an instrumental pre-requisite for enhancing national potential to achieve Nepal’s national shared goals on SDG. Implications: Nepal needs immediate goals diffusion with appropriate resources allocation for each participant of sustainable development.